Weight representations of affine Kac-Moody algebras and small quantum groups - Arakawa, Tomoyuki; Creutzig, Thomas; Kawasetsu, Kazuya (Advances in Mathematics, 2025)
We study the weight modules over affine Kac-Moody algebras from the view point of vertex algebras, and determine the abelian category of weight modules for the simple affine vertex algebra Lk(sl2) at any non-integral admissible level k. In particular, we show that the principal block of the category of weight modules over admissible Lk(sl2) is equivalent to that of the corresponding (unrolled) small quantum group.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Quantum groups; Vertex algebras